Legal Analysis of The Supreme Court Decision Number 5296 K/Pdt/2024 Concerning Customary Land Disputes Between Families - Sara Delima Putri Siagian; Widodo Ramadhana (Universitas Medan Area, 2026)
This study aims to analyze the juridical construction applied in Supreme Court Decision Number 5296 K/Pdt/2024, examine its implications for the protection of customary inheritance rights, and assess the extent to which the decision reflects the principles of justice, legal certainty, and expediency. The research employs a normative juridical method with statutory and case approaches, analyzed descriptively and analytically through primary, secondary, and tertiary legal materials. The results indicate that the Supreme Court tends to emphasize formal evidentiary aspects and physical control over land as the primary basis for determining rights. Consequently, the juridical construction applied is more oriented toward positive civil law rather than customary law, which is genealogical and communal in nature. The implication of this decision is the weakening of the protection of customary inheritance rights, as ownership claims based on kinship are not adequately recognized without physical possession or formal administrative evidence. This condition contributes to a paradigm shift from communal ownership toward the individualization of land rights. Furthermore, from the perspective of the three fundamental legal values, the decision reflects legal certainty to a certain extent but falls short in achieving substantive justice and expediency. Legal certainty is attained through clear evidentiary standards; however, justice for customary heirs is overlooked, potentially leading to long-term social consequences, including the erosion of customary law. Therefore, this study underscores the need for a more proportional integration between customary law and positive law in judicial practice to produce decisions that are not only legally certain but also just and beneficial for societ.